DIFFERENT TYPES OF 24-HOUR INTRAOCULAR PRESSURE CURVES IN PATIENTS WITH CATARACT AND OCULAR MANIFESTATIONS OF PSEUDOEXFOLIATION SYNDROME - M. Z. Frankovska-Gerlak; T. V. Sokolovskaya; P. E. Brizhak; V. S. Chubar (Офтальмохирургия, 2015)
Background. The significant diurnal fluctuations of intraocular pressure (IOP) remain one of the main factors that reflect the violation of ocular hydrodynamics. Nowadays, in the literature there is no data about the types of diurnal intraocular pressure curves in patients with pseudoexfoliation syndrome (PEX).Purpose. To study the types of 24-hour intraocular pressure curves in patients with ocular manifestations of pseudoexfoliation syndrome (PEX).Material and methods. The examination included 240 eyes of 120 patients aged 54-84 years with the diagnosis of complicated cataract and the PEX. The diurnal tonometry was conducted using the Maklakov tonometer during 24 hours with the 3-hour interval.Results. Based on our research for the patients with PEX four types of the IOP curves were detected: «unimodal», «bimodal », «flat», «inverse». First three types of curves have broad brandish of IOP fluctuations (more than 5mmHg). «Bimodal» type of curve was considered as the most unfavorable for ocular hydrodynamics. It was detected, that the type of 24-hour IOP curve in patients with PEX depends on the initial IOP level, degree of PEX manifestations, thickness of the lens and also on the presence of concomitant cardio-vascular diseases.Conclusions. The most characteristic types of 24-hour IOP curves in patients with PEX are: «unimodal», «bimodal», «flat», «inverse».